52.0k views
0 votes
Formula of a square minus b square​

User Gary Paluk
by
5.0k points

2 Answers

3 votes

According to the question


\large\bf{\orange{ \implies}} \: \tt \: {a}^(2) \: - \: {b}^(2)


\large\bf{\pink{ \implies}} \: \tt \: (a + b) \quad \: (a - b)


\large\bf{\pink{ \implies}} \: \tt \: a \: (a - b) \quad \: b \: (a - b)


\large\bf{\pink{ \implies}} \: \tt \: {a}^(2) \: - \: ab \: + \: ba \: - \: {b}^(2)


\large\bf{\pink{ \implies}} \: \tt \: {a}^(2) \: - \: ab \: + \: ab \: - \: {b}^(2)


\large\bf{\pink{ \implies}} \: \tt \: {a}^(2) \: - \: \cancel{ab} \: + \: \cancel{ab} \: - \: {b}^(2)


\large\bf{\pink{ \implies}} \: \tt \: {a}^(2) \: - \: {b}^(2)

User Petar Tahchiev
by
4.6k points
4 votes

Answer:

(a+b)(a-b)

Explanation:


\\ \sf\longmapsto (a+b)(a-b)


\\ \sf\longmapsto a(a-b)+b(a-b)


\\ \sf\longmapsto a^2-ab+ba-b^2


\\ \sf\longmapsto a^2-ab+ab-b^2


\\ \sf\longmapsto a^2-b^2

User Demeteor
by
5.6k points